Ripensare l’inclusione sociale nella prospettiva della sostenibilità (Stato, Chiese e pluralismo confessionale, 2023)
Re-thinking social inclusion in the sustainability’s perspectiveABSTRACT: This essay critically discusses some theoretical problems related to the relationship between social inclusion and sustainability. In particular, it highlights that this is a two-way relationship that takes place within the representation of a concrete universal. The reflection is divided into three moments: first, the concept of sustainability is investigated in relation to the idea of future and then the concept of inclusion is investigated in relation to both identity and participation.SOMMARIO: 1. Premessa - 2. Un futuro possibile, un futuro in comune - 3. Inclusione e identità - 4. Inclusione e partecipazione.